2015
DOI: 10.1016/j.jsha.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Spirometric values and chest pain intensity three days post-operative coronary artery bypass graft surgery

Abstract: The current study findings rejected the examined hypothesis that reduction of post-operative chest pain intensity would be associated with improvement in the spirometric values for patient underwent coronary artery bypass graft surgery. There was no significant relationship between the chest pain intensity and any of the spirometric values at any of the 3 post-operative days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
3
0
2
Order By: Relevance
“…However, this study was unable to identify which subtype of surgery was significantly associated with pain. A previous study identified that patients having CABG with Left Internal Mammary Artery (LIMA) and valvular surgery were more likely to have higher levels of pain than those having CABG without LIMA [21, 22]. The IMA grafting causes trauma to the internal thoracic cage, which increases the intensity of chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was unable to identify which subtype of surgery was significantly associated with pain. A previous study identified that patients having CABG with Left Internal Mammary Artery (LIMA) and valvular surgery were more likely to have higher levels of pain than those having CABG without LIMA [21, 22]. The IMA grafting causes trauma to the internal thoracic cage, which increases the intensity of chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Os resultados obtidos no presente estudo vão de encontro à literatura ao evidenciar a diminuição dos volumes pulmonares após procedimentos cirúrgicos, principalmente no pós-operatório imediato [10][11][12] . Tanto que Cardoso et al 13 , ao submeterem sua amostra a coleta dos volumes pulmonares e PFE no pré-operatório, pós-operatório imediato e pré-alta hospitalar, constataram que no pós-operatório imediato os pacientes apresentaram menor fluxo expiratório e já os valores coletados no pré-operatório, foram superiores aos demais, estando em concordância com o presente estudo onde os valores coletados após o procedimento cirúrgico foram menores aos que antecederam a cirurgia e os avaliados na UTI (pós-operatório imediato) foram inferiores aos aferidos na enfermaria (pré-alta hospitalar).…”
Section: Fisioterapiaunclassified
“…Spirometry tests performed before surgery provide measurable data regarding the functioning of the respiratory system, informing about the occurrence of respiratory disorders and indicating potentially increased risk of complications in the early post-operative period. The studies have shown that spirometry performed prior to and after the surgery can be regarded as a useful and repeatable tool to provide information about the status of the respiratory system’s capacity and function [ 15 , 16 , 17 ]. The use of methods allowing an accurate analysis of the respiratory system before and after surgery makes it possible to design individual physiotherapy plans, reducing the number of pulmonary complications after surgery and qualifying the patients for certain cardiac rehabilitation processes.…”
Section: Introductionmentioning
confidence: 99%